In the Contemporary Era of Artificial Intelligence, the Trajectory of Orthodontics: Past and Future Perspectives - A Narrative Review - Kanza Tahir; Afeefa Abul Barakaat; Mubassar Fida; Rashna Hoshang Sukhia (Taylor & Francis Group, 2024)
Objective To explore the evolution of orthodontics with the integration of Artificial Intelligence (AI), highlighting past achievements and future directions in diagnostics, treatment planning, and patient engagement.Methods A review of the literature was conducted to examine the historical progression of orthodontics, with a specific focus on the transformative role of AI. Key areas of focus include diagnostic accuracy, virtual surgical planning, and teledentistry. The review also discusses the clinical and non-clinical applications of AI in orthodontics and the challenges faced in its widespread adoption.Results AI has significantly improved diagnostic precision through automated cephalometric analyses. Personalized treatment planning and AI-driven virtual simulations have optimized orthognathic surgery. AI tools enhance patient communication and engagement through virtual assistants and telemedicine platforms. Challenges such as data security, ethical concerns, and financial barriers limit AI's seamless integration into orthodontics.Conclusion AI is revolutionizing orthodontics, enhancing diagnostics, treatment planning, and patient experience. Despite significant advancements, the integration of AI requires careful consideration of ethical, financial, and data security issues to ensure responsible and sustainable use in the field.